Tennis as Social Mobilization to Achieve the American Dream in the Film King Richard (2021) - Haekal Ramadhan; Akhmad Zakky (Litteratura: Jurnal Bahasa dan Sastra, 2024)
This study investigates the influence of tennis on the social mobility of an African-American family and how it shapes their pursuit of the American Dream. Employing qualitative research methods, this study utilizes elements of mise-en-scène in film analysis and social mobility theory to comprehensively explore how an African-American family uses tennis as a means to achieve their American Dream. The research reveals that Richard Williams' journey as a Black man determined to guide his daughters, Venus and Serena, to become world tennis champions, challenged deep-rooted racial barriers within American society. Furthermore, motivation, education, and achievement were significant factors influencing the upward social mobility of the Williams family. Despite not coming from a high social status background, the Williams family used tennis as a pathway to achieve their American Dream. This research argues that tennis broke societal boundaries and cemented the Williams family's legacy as a living embodiment of the American Dream. Their story stands as a testament to the boundless possibilities that determination and resilience through sports can offer, even when confronted with significant racial challenges and social disparities.